Hubungan Durasi dan Postur Duduk Terhadap Keluhan Low Back Pain pada Mahasiswa Kedokteran - Jocelyn Koswara; Yetty Machrina; Mahrani Lubis; Rina Amelia (Scripta Score Scientific Medical Journal, 2024)
Background: Low Back Pain (LBP) is the most common musculoskeletal disorder in the community with a global prevalence of 15-45% each year. Medical students are prone to LBP due to several risk factors such as long sitting duration and improper sitting posture during lectures. Objectives: This research is performed to determine the correlation between the duration and sitting posture during lectures on the incidence of LBP in medical students at Universitas Sumatera Utara (USU). Methods: This study used an analytical descriptive research design with a cross-sectional approach conducted in April 2023 at the Faculty of Medicine, Universitas Sumatera Utara. The sampling technique used is simple random sampling with 147 medical students selected as the research sample. Data was obtained from filling out PAD and BAPHY questionnaires. A Chi-square test was used to explore the association between the two variables and LBP while the logistic regression test was used to identify the dominating causes generating LBP. Result: The study's findings revealed that 40.1% of students reported having LBP problems, 72.1% reported sitting for more than seven hours, and 33.3% reported having a bad sitting posture. Chi-square analysis revealed a significant correlation between sitting duration and posture on complaints of LBP (RR = 1.69, p = 0.041 and RR = 1.69, p = 0.009). At a risk of 2,438 times, sitting position is the main factor contributing to LBP among medical students at USU. Conclusion: This research showed a correlation between duration and sitting posture on the incidence of LBP.